Twilight of Utopias: Julian and Aldous Huxley in the Twentieth Century - Deese, R. S. (Journal for the study of religion, nature and culture, 2011)
The biologist Julian Huxley and his younger brother, the novelist Aldous Huxley, each presented a distinct approach to utopian thought in the twentieth century. Julian Huxley sketched a vision of ideal polity that was nothing less than global, calling for the creation of a uni?ed world culture, a new religion predicated on the methods and discoveries of evolutionary biology, and, ultimately, the emergence of a global government. Aldous Huxley’s vision of utopia was deliberately local, based on his view that the machinations of large states, however well intentioned, were a threat to human liberty. Island, Aldous Huxley’s utopian novel of 1962, depicts a small cooperative society, employing low-impact technologies while draw¬ing its worldview from a combination of modern science and Mahayana Buddhism. The distinct visions of the Huxley brothers did share one common trait which remains resonant today. Each identi?ed ecological sustainability as the primary foundation for any plausible utopia.